Antimicrobial Effects of Propolis Ethanol Extract Tetragonula laeviceps Against Bacteria Methicillin Resistant Staphylococcus aureus - Phalosa Sahasika Sri Bharata (Pelopor Publikasi Akademika, 2023)
Staphylococcus aureus bacteria, especially Methicillin Resistant Staphylococcus aureus (MRSA), is one of the main causes of antibiotic resistance. MRSA is a bacteria that is resistant to the ?-lactam class of penicillin antibiotics. MRSA infections can cause a variety of health problems, including skin infections, pneumonia, and bacteremia. This problem requires alternative resources that can be an option. Propolis from the stingless bee species Tetragonula laeviceps can be a potential alternative for treating MRSA infections. This research is classified as a true experiment with a posttest control group design. The concentration of propolis ethanol extract tested was 20%; 10%; 5%; 2.5%; 1.25%; and 0.625% in the diffusion and dilution methods. These two methods provide assessment output in the form of inhibition zone diameter, minimum inhibition concentration, and minimum bactericidal concentration. The data obtained will be tested statistically using One-way Anova and Fisher's exact tests. Test results show that the ethanol extract of Tetragonula laeviceps propolis has an antimicrobial effect against MRSA bacteria. The diffusion test showed that the average diameter of the inhibition zone formed by the ethanol extract of propolis successively from a concentration of 20% to 1,25% with six repetitions was 12.7 ± 1.23 mm; 11.36 ± 0.67 mm; 10.24 ± 0.61 mm; 7.59 ± 1.69 mm; and 6.5 ± 1.14 mm. From these averages, the One-Way Anova test revealed a statistically significant difference in the diameter of the inhibition zone (F(7,40) = [ 192.79], p = 0.000).